Prevalence and clinical profile of heart failure patients with atrial fibrillation in a tertiary hospital in Kano, Nigeria - Sadiq Hassan Ringim; Usman Muhammad Ibrahim; Sabiu Mohammed Hamza; Faisal Saleh Dankishiya; Muhammad Sani Mijinyawa; Mahmoud Umar Sani (Nigerian Postgraduate Medical Journal, 2023)
Introduction: Atrial fibrillation (AF) is one of the most prevalent sustained arrhythmias that is seen in clinical practice. AF commonly coexists with heart failure (HF) and there is growing evidence that it confers an adverse prognostic impact on the natural course of the disease. We set out to describe the prevalence and clinical profile of HF patients with AF in Aminu Kano Teaching Hospital (AKTH), Kano, Nigeria. Materials and Methods: We conducted a cross-sectional study of all adults aged 18 years and above, who presented at the AKTH, Kano, and were hospitalised for HF. Those who consented were consecutively recruited into the study. Sociodemographic and clinical characteristics of patients at presentation were documented. Thromboembolic risk was assessed using CHA2DS2-VASc scoring system. A 12-lead electrocardiogram recording was obtained from each of the recruited patients to confirm the presence of AF. The prevalence of AF was determined amongst the admitted HF patients. Those with AF were compared with those without AF in terms of sociodemographic and clinical characteristics. Results: A total of 240 Nigerians were recruited. Sixty per cent were female and the whole group had a mean age of 50.85 ± 18.90 years. The prevalence of AF was found to be 12.5% amongst the recruited HF patients. The HF patients with AF had a significantly higher mean age (58 ± 16.7 years vs. 49.8 ± 19.0 years) (P = 0.021), and they also had a higher prevalence of palpitation and body swelling. The mean CHA2DS2-VASc score of the AF patients was 3.4 ± 1.0. Conclusion: AF is prevalent amongst HF patients in our environment with high thrombotic risk. More studies are needed to fully study the prevalence of AF and its clinical profile amongst HF patients in our country.